Strategi Manajemen BK dalam Menangani Problematika Karier Siswa SMA di Era Disrupsi - Nurul Fazria; Fratiwi, Rahmi; Suhaili, Neviyarni; Syukur, Yarmis (Media Manajemen Pendidikan, 2025)
This study explores the career challenges faced by high school students in the disruption era and the management strategies of guidance and counseling (GC) to address them. The objective is to identify students' career challenges and formulate effective GC strategies to enhance their independence and career readiness. The research method employed a Systematic Literature Review (SLR) of 30 articles from international and national journals published between 2020 and 2025, selected based on their relevance to GC and student career issues. Findings indicate that students face job market uncertainties, difficulties in recognizing their potential, and a lack of soft skills and digital literacy. Effective GC strategies include student needs analysis, the use of technologies such as cybercounseling and gamification, interest-based differentiated approaches, and professional training for GC teachers. In conclusion, the integration of technology and humanistic approaches in GC management can improve students' career readiness, although challenges such as the digital divide require cross-sectoral collaboration.